Risk Factors for Acute Respiratory Infections in Children Between 0 and 23 Months of Age in a Peri-Urban District in Pakistan: A Matched Case–Control Study - Mir, Fatima; Ariff, Shabina; Bhura, Maria; Chanar, Suhail; Nathwani, Apsara Ali; Jawwad, Muhammad; Hussain, Amjad; Rizvi, Arjumand; Umer, Muhammad; Memon, Zahid; Habib, Atif; Soofi, Sajid Bashir; et al. (Frontiers in Pediatrics, 2022)
Background Acute Respiratory Infection accounts for nearly 15% of all childhood mortality, with children from rural areas at higher risk due to inaccessibility to healthcare facilities. Methods A retrospective 1:2 matched case-control study was conducted between October – December 2018 in Taluka Kotri, District Jamshoro of Pakistan. Cases were identified as children between 0-23 months of age with a history of fever, cough, sore throat, fast breathing, difficulty breathing or chest indrawing in the two weeks prior to the survey. Controls were participants without symptoms of ARI, matched based on age in months. Data analysis was conducted using STATA version 15. Univariate and multivariable conditional logistic regression to identify factors associated with ARI, and p<0.05 was considered statistically significant. Results We identified 1071 cases of ARI who were marched with 2142 controls. Multivariable analysis revealed that female gender (OR 0.78, 95% CI: 0.67-0.91), exclusive breastfeeding (OR 0.81, 95% CI: 0.69-0.97), and comorbidity with diarrhea (OR: 1.64, 95% CI: 1.40-1.91) were significantly associated with ARI. Conclusion Pakistan continues to progress towards reducing childhood mortality, particularly ARI-related deaths, for which it bears a great burden. This study identifies risk factors that could open grounds for further programmatic implications in targeting a multifaceted approach to reducing incidences of ARI in the country.